In the Eye of the Covid-19 Storm: A Web-Based Survey of Psychological Distress Among People Living in Lombardy - Saita, Emanuela; Facchin, Federica; Pagnini, Francesco; Molgora, Sara (Frontiers in Psychology, 2021)
In March 2020, the World Health Organization announced the Covid-19 outbreak a pandemic and restrictive measures were enacted by the Governments to fight the spread of the virus. In Italy, these measures included a nationwide lockdown, with limited exceptions including grocery shopping, certain work activities, and healthcare. Consistently with findings from previous studies investigating the psychological impact of similar pandemics (e.g., Severe Acute Respiratory Syndrome [SARS]), there is evidence that Covid-19 is associated with negative mental health outcomes. Given this background, we conducted a cross-sectional study aimed at investigating the impact of the Covid-19 pandemic and the subsequent restrictive measures imposed by the government on the psychological health of Italian men and women aged ≥ 18 years and living in Lombardy, the worst-hit region. The study also aimed at identifying what factors are associated with specific psychological outcomes. Thus, we developed an online survey that included a researcher-made questionnaire to collect sociodemographic, household, general health, and pandemic-related information. The Generalized Anxiety Disorder-7, the Patient Health Questionnaire-9 and the Perceived Stress Scale were used to assess anxiety, depression, and perceived stress, respectively. We found that younger age, greater concerns about the pandemic, female gender, being unmarried, not having children, and being a student were associated with worse psychological health. These findings may provide further insight into the risk factors associated with negative psychological outcomes during the current pandemic, with identification of vulnerable groups. This body of evidence may help professionals implement targeted psychosocial treatment and prevention programs.